HUBUNGAN ANTARA POLA KONSUMSI FAST FOOD DAN AKTIVITAS FISIK DENGAN KEJADIAN GIZI LEBIH REMAJA DI SMA KECAMATAN SUMBERSARI - Fidia, Andryana Martha; Ningtyias, Farida Wahyu; Astuti, Nur Fitri Widya (LPPM Institut Kesehatan Helvetia, 2024)
Background; overweight is a global epidemic that is becoming a health problem including in Indonesia due to its increasing prevalence. Adolescence is a crucial age for overweight. Overweight that happens in adolescence will continue into adults and have a high chance of developing degenerative diseases (diabetes mellitus type 2 and cardiovascular disease). The main factor in overweight because imbalance between energy intake and energy output, which is influenced by high consumption of fast food and low physical activity. Objectives; analyzing the association between fast food consumption and physical activity with overweight incidence in adolescent. Methods; this study was an observational analytic study with a cross-sectional design. The research time began in September-February 2024 at Senior High School in Sumbersari District. Sampling was done by proportionate random sampling. The research sample was 95 respondents. The independent variables of this study were fast food consumption and physical activity, while the dependent variable was overweight. This research data analysis used Chi-Square test. Results; the results of this study show that there is a association between fast food consumption based on type and frequency (processed chicken such as fried chicken, french fries, instant noodles, fried rice, and meatballs) with overweight incidence in adolescent (p0,05). However, there is no association between the total energy consumption of fast food with overweight incidence (p0,0001). There is an association between physical activity with overweight incidence in adolescents (p0,0001). Conclusion; fast food consumption (type and frequency) and physical activity were associated with overweight incidence in adolescents. However, there was no association between the total energy consumption of fast food with overweihgt incidence in adolescents.